Clinical and Epidemiological Aspects of Parkinson's Disease in the South of Western Siberia - Rozhdestvensky, Alexey Sergeevich; Delov, Roman Andreevich; Marks, Elena Andreevna; Gaponenko, Ivan Aleksandrovich; Khanokh, Elena Vladimirovna (Frontiers in Neurology, 2020)
Тhe article is devoted to one of the most common neurodegenerative diseases in the world - Parkinson's disease (PD), the prevalence of which in Russia reaches 140-150 people per 100 thousand people. The clinical and anamnestic profile of a patient with PD is presented, the prevalence of motor and non-motor symptoms is reflected, and a comparative characteristic of the neurological deficit in the Siberian population of patients with other cohorts of patients with Parkinson's disease is presented. We studied 140 patients with Parkinson's disease. A comprehensive assessment of neurological status was performed using the “Unified Parkinson's Disease Rating Scale (UPDRS). In addition, we used the Beck Depression and MoCA scale - test. The cohort of the study was dominated by overweight patients with a higher level of education, with concomitant arterial hypertension, coronary heart disease and dyslipidemia. The prevalence of motor and most non-motor symptoms depends on the stage of the disease. The predominant form of the disease was a mixed form, which was also noted in research cohorts in Canada and the UK. The Siberian cohort tends to be more prevalent in hyposmia, daytime sleepiness, orthostatic hypotension, and depressive and REM disorders. Our data show the importance of a comprehensive assessment of both motor and non-motor neurological deficits, as well as the analysis of comorbid disorders and risk factors for the occurrence and progression of Parkinson's disease. They also show the prevalence of certain motor and non-motor symptoms in the Siberian cohort of patients with Parkinson's disease.